The Influences of Work Environment and Burnout on the Job Satisfaction of Transjatim Bus Operational Crew Corridor 5 Surabaya - Bangkalan Route - Zulkarnain, Farhan Nauval; Santoso, Bowo; Dewanti, Mentari Clara (Manunggal Halim Jaya, 2026)
This study aims to analyze the influence of work environment and burnout on job satisfaction among operational crew members of Transjatim Bus Corridor 5, which serves the Surabaya–Bangkalan route. The research employed a quantitative approach using a survey method with a structured questionnaire distributed to 40 respondents, consisting of drivers and attendants. The sampling technique used was saturated sampling, ensuring that all members of the population were included. Data analysis was conducted using Structural Equation Modeling with Partial Least Squares (SEM-PLS) Version 4. The findings reveal that the work environment has a positive and significant effect on job satisfaction, while burnout has a negative and significant effect. This indicates that better workplace conditions, such as supportive facilities, harmonious coworker relationships, and sufficient rest areas, contribute to higher job satisfaction levels among crew members. Conversely, high levels of burnout, including mental and emotional exhaustion, reduced motivation, and increased interpersonal conflict, significantly reduce job satisfaction. The study highlights contextual challenges faced by the operational crew, such as tight bus schedules, limited rest time, overcrowded vehicles, and cultural differences between Surabaya and Bangkalan-based personnel. These challenges contribute to emotional fatigue and workplace stress, reinforcing the negative impact of burnout on employee satisfaction. The study emphasizes the need for managerial interventions to enhance the quality of the work environment and implement burnout mitigation strategies. The results provide important implications for public transportation management, especially in intercity routes, suggesting that improving the work environment and addressing burnout are critical for sustaining job satisfaction and service quality.